DIETA DE Crenicichla iguassuensis (PISCES: CICHLIFORMES: CICHLIDAE), ESPÉCIE ENDÊMICA DO RIO IGUAÇU, BRASIL. - SOUZA, Tuiza de; ABELHA, Milza Celi Fedatto; DIAS, Rosa Maria; KASHIWAQUI, Elaine Antoniassi Luiz (ANAIS DO ENIC, 2025)
-